Characterization Of Filled Epoxy Thin Film Composites For Dielectric Application - Poh, Chen Ling (2015)
In this research, dielectric, mechanical and thermal properties of various types of fillers filled epoxy thin film composites were studied. The fillers and epoxy were prepared using ultrasonic mixing and the thin film composites were fabricated using spin coating method. In the first stage, the properties of mineral calcium carbonate (mineral CaCO3) and precipitated calcium carbonate (precipitated CaCO3) filled epoxy thin film composites were investigated. It was found that precipitated CaCO3 exhibited higher dielectric properties and tensile strength than mineral CaCO3 whereas mineral CaCO3 exhibited higher thermal properties and modulus than precipitated CaCO3. In the second stage, the properties of various types of fillers (precipitated CaCO3, Barium titanate (BaTiO3) and multi-walled carbon nanotube (MWCNT)) were investigated. It was found that BaTiO3 and MWCNT exhibited higher specific capacitance and dielectric constant than precipitated CaCO3. Since dielectric and capacitance properties are important for the capacitor application, MWCNT was chosen in the functionalization study in the third stage. Various types of functionalization using polyoxyethylene octyl phenyl ether (Triton X-100), sodium dodecyl sulfate (SDS), and 3-(aminopropyl)triethoxy silane (AMPTES) treated MWCNT were used to treat MWCNT. It was found that treated MWCNT had improvement in dielectric and mechanical properties. Slightly similar dielectric properties were observed in the comparison of two different epoxies (DER 332 epoxy and OP 392 epoxy) with 1.5 vol% untreated MWCNT and Triton X-100 and SDS treated MWCNT. OP 392 epoxy thin film composites exhibited higher glass transition temperature (Tg) and lower tensile strength compared to that of DER 332 epoxy thin film composites. Overall, Triton X-100 treated MWCNT filled OP 392 epoxy thin composite is the most suitable material for the dielectric application